Drug Users and Cannabis - Ruken Macit (Journal of Economy Culture and Society)
Drug abuse is a major social problem faced by all countries. From the past to the present, although there are many different drugs, some have a more important place than others. One of the most important drugs in the drugs trade is cannabis which is the most produced and most used drug substance in the world and in Turkey. It has a different position among other drugs because it is herbal. Over time, this feature has caused a common belief in society that it is harmless. Despite this general belief, it has been proven by many studies that cannabis causes serious damage to individuals’ physical and mental well-being. In this research, semi-structured interviews were conducted with 20 cannabis users living in the Turkish cities of Istanbul (7), Mersin (7) and Diyarbakır(6). In this context, issues such as how cannabis users experience cannabis for the first time, how they make it permanent, and what they experience under the influence of cannabis are analyzed. The conclusion reached is that friends and peers have an important role in drug use. According to the findings, the first experience and the experience when they get high provides important information on drug use. This information is thought to be effective in fighting drug abuse.